A CRITICAL STUDY ON THE ROLE OF ODR IN INSOLVENCY LAW WITH REFERENCE TO INDIA AND VIETNAM IN THE CONTEXT OF GLOBAL HEALTH TRANSITIONS - Jyotirmoy Banerjee; Dr. Bhrigu Raj Maurya (South Eastern European Journal of Public Health, 2025)
The integration of ODR in insolvency law has emerged as a critical mechanism for ensuring efficiency, accessibility, and transparency in resolving financial distress cases, particularly in countries undergoing economic and health transitions like India and Vietnam. The study critically examines the evolution of insolvency laws in both nations, focusing on the role of ODR in enhancing dispute resolution efficiency. While India’s IBC, 2016, has undergone multiple amendments, its adoption of ODR remains limited. Similarly, Vietnam’s Bankruptcy Law, 2014, lacks explicit provisions for digital dispute resolution, necessitating legal reforms to streamline insolvency processes. The impact of global health transitions on business insolvency further underscores the need for swift and cost-effective resolution mechanisms. The rise in medical bankruptcies due to economic instability and public health crises has increased the demand for ODR platforms that ensure timely resolutions. The adoption of emerging technologies such as AI, blockchain, and virtual courts can revolutionize insolvency dispute resolution, as seen in China’s internet courts, which have reduced case resolution times by 35%. However, significant challenges persist, including regulatory inconsistencies, data security concerns, and digital literacy barriers. The absence of a dedicated institutional framework for ODR in insolvency proceedings in both India and Vietnam further limits its widespread adoption. International cooperation and best practices from frameworks like UNCITRAL’s Model Law on Electronic Commerce and the Singapore Convention on Mediation offer valuable insights for developing structured ODR mechanisms. Policy recommendations include legal amendments to explicitly recognize ODR, technological integration to enhance efficiency, and regional collaborations to harmonize insolvency resolution frameworks. Strengthening institutional support and embracing global best practices will enable India and Vietnam to develop robust digital dispute resolution ecosystems, fostering economic resilience and enhancing creditor confidence in insolvency proceedings.